# Revision history [back]

### how to get simplified result of solving equation

Hi there!

In a linear algebra assignment I have the following equation I need to find a solution for:

-2sqrt(3)sin(t)^2+2cos(t)sin(t)+sqrt(3)==0. I know the result is pi/3.

Now, when I use solve, solve(-2sqrt(3)sin(t)^2+2cos(t)sin(t)+sqrt(3)==0, t). I get:

[sin(t) == -1/6sqrt(3)(sqrt(cos(t)^2+6)-cos(t), sin(t) == 1/6sqrt(3)sqrt(cos(t)^2+6)+cos(t))].

How do I use the solve function to get the more simplified result?

NB: I have also tried to use find_root and different simplify functions, but also without any luck. I am new to sage, so it is quite possible that I don't know a specification to the solve function which I should use.

Sincerly Simon 2 No.2 Revision

### how to get simplified result of solving equation

Hi there!

In a linear algebra assignment I have the following equation I need to find a solution for:

-2sqrt(3)sin(t)^2+2cos(t)sin(t)+sqrt(3)==0. -2*sqrt(3)*sin(t)^2+2*cos(t)*sin(t)+sqrt(3)==0. I know the result is pi/3.

Now, when I use solve, solve(-2sqrt(3)sin(t)^2+2cos(t)sin(t)+sqrt(3)==0, t). solve(-2*sqrt(3)*sin(t)^2+2*cos(t)*sin(t)+sqrt(3)==0, t). I get:

[sin(t) == -1/6sqrt(3)(sqrt(cos(t)^2+6)-cos(t), -1/6*sqrt(3)*(sqrt(cos(t)^2+6)-cos(t), sin(t) == 1/6sqrt(3)sqrt(cos(t)^2+6)+cos(t))].1/6*sqrt(3)*sqrt(cos(t)^2+6)+cos(t))].


How do I use the solve function to get the more simplified result?

NB: I have also tried to use find_root find_root and different simplify functions, but also without any luck. I am new to sage, so it is quite possible that I don't know a specification to the solve function which I should use.